Triton-X amphoteric surfactant as drag reducing agent in aqueous media flowing in pipelines with different pipe diameters - Zainur Azizi, Zakaria (2009)
In this study the effect of the presence of a drag reducing agent (DRA) on the pressure drop in co-current horizontal pipes carrying flow of water is investigated. An experimental set-up is erected. The tested fluid was water and aqueous solution of Triton X-100 surfactant with 50 ppm (ppm-part per million), 100 ppm, 200 ppm and 300 ppm weight concentration of Triton X-100. The test section of the experimental set-up is consisted of three different pipe diameter and testing section length. The experimental was doing with 0.5 inch, 1.0 inch, 1.5 inch ID and 0.5 m long, 1.0 m long and 1.5 m long. Water also was pumped with five different fluid flow rates which is for each pipe diameter have a differ values of volumetric flow rate setting. The percent drag reduction (%DR) is calculated using the obtained experimental data, in presence of the DRA. The results show that addition of DRA could be effective up to some doses of DRA. Not only that, with smaller pipe diameter, performances of drag reduction occur is much better than larger pipe diameter. A maximum %DR of about 73 is obtained for 300 ppm concentration of Triton X-100. This is shows that, the energy consumption for pumping system will be decrease about 73%. When the energy consumption is decrease, the costing for installation pumping system also will be decreased.